Screening exons 16 and 17 of the amyloid precursor protein gene in sporadic early-onset Alzheimer’s disease - Barber, Imelda S.; García-Cárdenas, Jennyfer M.; Sakdapanichkul, Chidchanok; Deacon, Christopher; Zapata Erazo, Gabriela; Guerreiro, Rita; Bras, Jose; Hernandez, Dena; Singleton, Andrew; Guetta-Baranes, Tamar; Braae, Anne; Clement, Naomi; et al. (Elsevier, 2016)
Early-onset Alzheimer’s disease (EOAD) can be familial (FAD) or sporadic (sEOAD); both have a disease onset ≤ 65 years of age. 451 sEOAD samples were screened for known causative mutations in exon 16 and 17 of the Amyloid Precursor Protein gene (APP). Four samples were shown to be heterozygous for one of three known causative mutations: p.A713T, p.V717I and p.V717G, this highlights the importance of screening EOAD patients for causative mutations. Additionally, we document an intronic 6 base pair (bp) deletion located 83 bp downstream of exon 17 (rs367709245, IVS17 83-88delAAGTAT), which has a nonsignificantly increased minor allele frequency in our sEOAD cohort (0.006) compared to LOAD (0.002) and controls (0.002). To assess the effect of the 6 bp deletion on splicing, COS-7 and BE(2)-C cells were transfected with a minigene vector encompassing exon 17. There was no change in splicing of exon 17 from constructs containing either wild type or deletion inserts. Sequencing of cDNA generated from cerebellum and temporal cortex of a patient harbouring the deletion found no evidence of transcripts with exon 17 removed.